2022
DOI: 10.3389/fpls.2022.1024353
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolism approach reveals difference of varieties of bud and relation among characteristics of grafting seedlings in Camellia oleifera

Abstract: Camellia oleifera is one of the essential wood oil trees in the world. C.oleifera was propagated by nurse seedling grafting. Since the scion of C.oleifera had a significant regulated effect on the properties of rootstock after grafting and impacted on the growth of the grafted seedlings, it was necessary to understand the characteristics of buds among varieties to cultivate high-quality grafted seedlings. The metabolome was thought to be a powerful tool for understanding connecting phenotype-genotype interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…This indicates that using only species as the selection criteria for oil tea rootstocks may pose a risk to yield quality after oil tea grafting. At the same time, it also indicates that the interaction between rootstocks and scions in Camellia oleifera is not only the regulation of root growth by scions [50][51], but also re ected in the in uence of fruit characteristics. Due to the signi cant impact of rootstocks on the physiological characteristics and other aspects of the growth and development of grafted plants, the reduction of scion growth is one of the most interesting phenomena.…”
Section: Discussionmentioning
confidence: 86%
“…This indicates that using only species as the selection criteria for oil tea rootstocks may pose a risk to yield quality after oil tea grafting. At the same time, it also indicates that the interaction between rootstocks and scions in Camellia oleifera is not only the regulation of root growth by scions [50][51], but also re ected in the in uence of fruit characteristics. Due to the signi cant impact of rootstocks on the physiological characteristics and other aspects of the growth and development of grafted plants, the reduction of scion growth is one of the most interesting phenomena.…”
Section: Discussionmentioning
confidence: 86%
“…This indicates that using only species as the selection criteria for oil tea rootstocks may pose a risk to yield quality after oil tea grafting. At the same time, it also indicates that the interaction between rootstocks and scions in C.oleifera is not only the regulation of root growth by scions [ 67 68 ], but also reflected in the influence of fruit characteristics. Due to the significant impact of rootstocks on the physiological characteristics and other aspects of the growth and development of grafted plants, the reduction of scion growth is one of the most interesting phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…It has an impact on the stability of the product. Research has found a significant rootstock and scion interaction in the grafted seedlings of C.oleifera [ 14 17 ], and scions control root growth after grafting [ 14 ], and the effect of scions on nutrient absorption [ 18 ]. There are significant differences in tree potential and growth among different varieties [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It measures a wide range of low‐molecular weight metabolites, including steroids, fatty acids, carbohydrates, and amino acids (Abadie et al, 2022; Chen et al, 2022). Finding the metabolites that correspond to each biological phenotype and then providing an understanding of the process involved are two important goals of metabolomics, bearing in mind that each plant variety has a unique metabolite type and correlation network relationship (Long et al, 2022). Despite its importance in understanding the associated biological processes, the possibility of metabolomics to acquire a full description of the processes may be limited due to the lack of an experimental database and advanced statistical and bioinformatics software requirements (Kind and Fiehn, 2006; Chen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%